Single layer graphene controlled surface and bulk indentation plasticity in copper. (March 2021) - Bahrami, F.; Hammad, M.; Fivel, M.; Huet, B.; D'Haese, C.; Ding, L.; Nysten, B.; Idrissi, H.; Raskin, J.P.; Pardoen, T.
Abstract: The impact of graphene reinforcement on the mechanical properties of metals has been a subject of intense investigation over the last decade in surface applications to mitigate the impact of tribological loadings or for strengthening purposes when dispersed into a bulk material. Here, the effect on the plastic indentation response of a single graphene layer grown on copper is analyzed for two configurations: one with graphene at the surface, the other with graphene sandwiched under a 100 nm thick copper cap layer. Nanoindentation under both displacement and load control conditions show both earlier and shorter pop-in excursions compared to systems without graphene. Atomic force microscopy reveals much smoother pile-ups with no slip traces in the presence of a surface graphene layer. The configuration with the intercalated graphene layer appears as an ideal elementary system to address bulk hardening mechanisms by indentation testing. Transmission electron microscopy (TEM) cross-sections below indents show more diffuse and homogeneous dislocation activity in the presence of graphene. 3D dislocation dynamics simulations allow unraveling of the origin of these 3D complex phenomena and prove that the collective dislocation mechanisms are dominantly controlled by the strong back stress caused by the graphene barrier. These results provide a quantitative understanding of the impact of graphene on dislocation mechanisms for both surface and bulk applications, but with an impact that is not as large as anticipated from other studies or general literature claims. Graphical abstract: Image 1 Highlights: Compare indentation of Cu films with or without graphene, with or without extra Cu cap layer. Presence of graphene leads to smaller pop-ins and smoother pile ups. TEM reveals more homogenous dislocation activity with graphene. Discrete dislocation dynamics simulations show large back stress with graphene. Effect of graphene on hardness is weak.